2009
DOI: 10.1111/j.1444-0938.2009.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of the cornea measured by the Ocular Response Analyzer and their association with intraocular pressure and the central corneal curvature

Abstract: Background:The aim of this study was to investigate the biomechanical properties of the cornea and their association with intraocular pressure (IOP), central corneal thickness (CCT) and the central corneal radius of curvature (Rc). Methods: Eighty-three eyes were divided into two groups. The biomechanical properties of the cornea were measured in 63 normal eyes and in 20 post-laser in situ keratomileusis (LASIK) eyes. The IOP, corneal hysteresis (CH) and corneal resistance factor (CRF) were measured by the Ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 17 publications
8
51
1
1
Order By: Relevance
“…8,16 In normal eyes, CH and CRF are known to be influenced by the corneal thickness, being higher in thicker corneas probably because of increased collagen. 17 Some studies have reported on corneal structural parameters affecting CH and CRF in normal eyes 3,4,17,18 ; however, few studies have reported on keratoconic and crosslinked KC eyes. 11,16,19 The Pentacam is a rotating Scheimpflug camera (Oculus Inc, Wetzlar, Germany) that is routinely used for evaluating the cornea and diagnosing keratoconus.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…8,16 In normal eyes, CH and CRF are known to be influenced by the corneal thickness, being higher in thicker corneas probably because of increased collagen. 17 Some studies have reported on corneal structural parameters affecting CH and CRF in normal eyes 3,4,17,18 ; however, few studies have reported on keratoconic and crosslinked KC eyes. 11,16,19 The Pentacam is a rotating Scheimpflug camera (Oculus Inc, Wetzlar, Germany) that is routinely used for evaluating the cornea and diagnosing keratoconus.…”
mentioning
confidence: 98%
“…The ORA uses a rapid air impulse and an advanced electro-optic system to assess changes in the corneal shape in response to indentation. 3 The corneal hysteresis (CH) and the corneal resistance factor (CRF) are the main biomechanical parameters derived through this deformation process. CH is a measure of corneal tissue properties that result from viscous damping, and CRF indicates the overall resistance of the cornea.…”
mentioning
confidence: 99%
“…These ranges were chosen in order to cover a very wide of possible inputs, including very extreme pathological conditions. [12][13][14]30,38 superior-inferior and nasal-temporal meridians with a sinusoidal fashioned density distribution as reported in literature [8,11]. The present modeling, if adapted to account for orthotropic reinforcement, may also be valuable for anticipating the patient-specific biomechanical limits of safe rehabilitating refractive surgery, in order to avoid unexpected iatrogenic keratoectatic catastrophic results.…”
Section: Discussionmentioning
confidence: 71%
“…However, the range of inputs that are permitted include severe pathological conditions and therefore this does not impose any clinical limitations (for the analysis and values please see the appendix). [12][13][14]30,38 Further improvements to this model may include adding orthotropic characteristics of the cornea in order to provide a more complete representation of corneal biomechanics. In the present framework it would be straight forward to do so by adding fiber elements in reinforced directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation